Ratification quotas in international agreements. An example of emission reduction - Simone Kohnz (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
This paper analyses the role of ratification quotas in multilateral agreements over emission reduction. The higher is the quota, the lower is the level of emissions in case the agreement comes into force, but the higher is also the risk of failure. In a setting with incomplete information, two country types and a binary contribution to the provision, I examine the differences between simultaneous and sequential ratification. When the benefits from emission of both types are smaller than the social costs, the outcome in the simultaneous case is essentially identical to the sequential case. The optimal quota is 100% and achieves the first best. With the high type's benefits exceeding the social costs, I find that the optimal quota is as small as possible, if ratification is simultaneous. In the sequential ratification case, I cannot determine the optimal quota. However, I find that the aggregate expected surplus decreases with respect to the simultaneous case.
urn:nbn:de:bvb:19-epub-900-7
Keywords: D71; H41; 330; public goods; international bargaining; ratfication; emission games